Strategies for Shaping the Identity of Novice Arabic Teachers in a Professional Education Program - Aulia Rahman; Bakri Muhammad Bakheet; Umi Machmudah; Moh. Buny Andaru Bahy; Nurhadi, Nurhadi; Muhammad Alfan (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study investigates the strategic formation of professional identity among novice Arabic teachers within a teacher professional education program. It aimed to delineate the core identity values fostered and to elucidate the specific strategies employed by the program to cultivate this identity. Employing a qualitative case study design, data were generated through direct observation and semi-structured interviews with program implementers, educators, and student teachers, selected via snowball sampling. Analysis involved a staged process of data reduction, coding, and categorization, framed by Uril Bahruddin's theory of language education development. The findings demonstrate that professionalism and learning are the central identity values instilled troughout the program. This identity, which serves as an indicator of professional competence, is systematically forged through a multi-faceted strategic approach that includes matriculation, targeted assignments, curated teaching materials, comprehensive assessment and evaluation, and activity-based methods. These strategies effectively guide novice Arabic teachers in developing their professional identity and shaping their long-term teaching trajectory.